Effect of adding Au nanoparticles to TiO2 films on crystallization, phase transformation, and photocatalysis. Issue 4 (14th February 2018) - Wada, Noriyuki; Yokomizo, Yuji; Yogi, Chihiro; Katayama, Misaki; Tanaka, Atsuhiro; Kojima, Kazuo; Inada, Yasuhiro; Ozutsumi, Kazuhiko
Abstract: Abstract : To investigate the effects of adding Au nanoparticles (AuNPs) to TiO2 films on the crystallization, phase transformation, and photocatalysis, films of both TiO2 and TiO2 embedded with AuNPs (Au–TiO2 ) with various characteristics were prepared by using the dip-coating method with preheating and post-heating treatments. The AuNPs acted as anatase nucleation agents and crystallized a lot of small anatase crystals with sizes of tens of nanometers, which suppressed the growth of anatase crystals that are large enough for them to transform into rutile crystals, resulting in repression of the transformation from anatase into rutile. The AuNPs affected the progress of the photocatalytic and adsorption reactions, resulting in improved photocatalytic activity. Of all the films we tested, the Au–TiO2 film preheated at 400 °C and post-heated at 400 °C (AT400-400), which consisted of small anatase crystals with high covalent character and high crystallinity, contained dispersed AuNPs with the smallest average crystallite size and showed the highest photocatalytic activity. This high activity resulted from the high reaction rate constants for adsorption and photocatalysis.